Israel Journal of Mathematics - London, Eran.; Linial, Nati.; Ziegler, Tamar; Kronberg, Daniel; SpringerLink (Online service) (Jerusalem : The Hebrew University Magnes Press : Imprint: Hebrew University Magnes Press.)
The Israel Journal of Mathematics is an international journal publishing high-quality original research papers in a wide spectrum of pure and applied mathematics. The prestigious interdisciplinary editorial board reflects the diversity of subjects covered in this journal, including set theory, model theory, algebra, group theory, number theory, analysis, functional analysis, ergodic theory, algebraic topology, geometry, combinatorics, theoretical computer science, mathematical physics, and applied mathematics. The Israel Journal of Mathematics is owned by the Hebrew University of Jerusalem and publishes for worldwide distribution under the Magnes Press. Since its inception in 1963, its volumes can be found in the libraries of major mathematical institutions around the world. More than 2300 pages per year are published. Impact Factor: 0.625 (2008) * Subject category "Mathematics": Rank 91 of 215 * Journal Citation Reports®, Thomson Reuters.
Keywords: Mathematics; Algebra; Group theory; Mathematical analysis; Analysis (Mathematics).; Applied mathematics; Engineering mathematics; Physics; Mathematics, general; Algebra; Group Theory and Generalizations; Analysis; Applications of Mathematics; Theoretical, Mathematical and Computational Physics